Self-image and subjective well-being in medical tourism: Role of age and behavior intentions - Loureiro, S.; Panchapakesan, P. (Proceedings of the International conference on Tourism and Ageing., 2016)
The current article intends to propose a conceptual framework that presents antecedents and outcomes of consumers (patients) desires to undergo medical tourism practices, as well as moderators that can strengthen or weaken the established relationships.